The contrasting effects of farm size on farm incomes and food production - Frederik Noack; Ashley Larsen (Environmental Research Letters, 2019)
Small-scale farming provides both food and livelihoods for the vast majority of the global poor. Thus, increasing and stabilizing farm incomes and food production in developing countries is fundamental to reducing global poverty. Policies for rural development such as improved access to non-agricultural incomes or land titling may benefit farmers, but they may also lead to farm consolidation with unintended consequences for aggregate food supply. Using a large panel dataset of rural households in Uganda, we parse apart how farm size affects the level and riskiness of agricultural incomes as well as of local food supply. Our findings indicate that while output per unit of land does decline with increasing farm size as suggested by previous literature, agricultural incomes increase with farm size. We show further that while the variance of agricultural incomes declines with increasing farm size, the variance of local food production increases with farm size. These results suggest that farmers benefit from larger farms, earning higher and more stable incomes while consumers suffer from lower and more volatile food supply.